(untitled) (The Conference Hub, 2025)
This article explores the impact of continuous assessment on English language learners’ motivation and academic achievement within a blended learning environment. With the growing adoption of digital tools and hybrid education models, it is crucial to examine how formative, ongoing assessment practices influence learners’ engagement and progress. The findings show that continuous assessment not only supports individual learning needs but also fosters a more motivating, student-centered learning atmosphere. This article aims to provide both theoretical insights and practical recommendations for English language educators.